Participatory aspects of strategic sustainable development planning in local communities: Experience of Lithuania - Čiegis, Remigijus; Gineitienė, Dalia (Technological and Economic Development of Economy, 2008)
While analysing the evolution of sustainable development concept as the basic criteria of periodisation, a number of dimensions could be used. Thus, it is possible to mark three stages in the development of the concept: a) two‐dimensional sustainability; b) three‐dimensional sustainability; c) four‐dimensional sustainability. Sustainable development should be implemented in all spheres and levels of life, estimating economic, social, ecological, territorial, political and institutional aspects. All dimensions of sustainability should be considered in the process of strategic sustainable development planning. Local communities understood that strategic sustainable development plans, which realize their willingness to live following the principles of sustainable development, are important. Different methods of public involvement were used when creating sustainable development strategies for local communities. Sustainable development concept, principles of sustainable development and strategic planning, methodology for strategic sustainable development planning, and participation of local communities are discussed in the article.Strateginio darnaus vystymosi aspektai vietinėse bendruomenėse: Lietuvos patirtisSantrauka. Šiame straipsnyje pristatoma darnaus vystymosi etapų koncepcija, kurią sudaro dviejų, trijų ir keturių dimensijų paradigmos. Planuojant strateginį darnų vystymąsi turėtų būti atsižvelgta į šiuos etapus. Dar visai neseniai Lietuvoje vietos savivaldos institucijos ir akademinė bendruomenė priėmė darnaus vystymosi principus, tačiau šiuo straipsniu siekiama parodyti vietinių bendruomenių nuostatas šiuo klausimu. Paaiškėjo, kad ne visos vietinės bendruomenės grupės (dalininkai) suvokia pagrindinius darnaus vystymosi principus, kyla nepasitikėjimas savivaldybės veiksmais ir priimamais nutarimais, kyla nesutarimų ir konfliktų grėsmė darnaus vystymosi strategijos bei planavimo procese dėl metodologijos spragų ir netikslumų.Reikšminiai žodžiai: darnus vystymasis, strateginis planavimas, vietinės bendruomenės, visuomeninis dalyvavimas, Lietuva.First published online: 21 oct 2010